Very high cycle fatigue and fatigue crack propagation behavior of selective laser melted AlSi12 alloy. (January 2017) - Siddique, Shafaqat; Imran, Muhammad; Walther, Frank
Highlights: Paper explores fatigue mechanisms of SLMed ALSi12 alloy in gigacycle fatigue. Base plate heating controls the cooling rate and the corresponding properties. Base plate heating improves the fatigue performance of SLM ALSi12 alloy. Base plate heating also improves the fatigue crack propagation behavior. Defect distribution dominates the microstructural effects on fatigue. Abstract: Selective laser melting is a maturing additive manufacturing process which has been studied in the recent years for processing different alloys. The focus, however, remained on the processibility, design considerations and static or quasistatic mechanical properties. For the application of the process for functional components, it is required that the process parts perform well in cyclic applications as well. The influence of processing parameters on the resulting part parameters and the corresponding fatigue behavior remains unaddressed. This study investigates the influence of base plate heating and post-process stress-relief on part properties like process-incited defects, which are critical for fatigue loading, for AlSi12 alloy. Investigations have been made for very high cycle fatigue as well as fatigue crack growth. To understand the fatigue phenomenon, characterization of basic material properties is also carried out. Results show that the material defects as well as microstructure is influenced by these parameters. The corresponding fatigue and crack growth behavior is improved by base plate heating which changes the fatigue crack initiation mechanisms as well. Relatively reduced thermal gradients by base plate heating helps improving the fatigue reliability by reducing the fatigue crack initiation from material defects.